2008
DOI: 10.1097/cji.0b013e3181611420
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Trial of Intranodal Injection of a Melan-A/MART-1 DNA Plasmid Vaccine in Patients With Stage IV Melanoma

Abstract: Nineteen patients with stage IV melanoma were treated in an escalating dose, phase 1 trial of a DNA plasmid vaccine pSEM. The plasmid encoded T-cell epitopes from differentiation antigens Melan-A/melanoma antigen recognized by T cells (MART)-1 and tyrosinase, encompassing amino acids 26-35 and 31-70 from Melan-A/MART-1, and 1-9 as well as 369-377 from tyrosinase. End points of the trial were safety, tolerability, and melanoma antigen-specific immunity by tetramer assay. Intralymph nodal infusions of the vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 42 publications
1
47
0
1
Order By: Relevance
“…Although the preclinical immunogenicity of this approach was superior to immunization using conventional means, 22 the immunological and clinical effects in humans were quite limited. 20,21 More recently, we showed in a preclinical model that an epitope-specific peptide boost after DNA vaccination achieved a significant amplification of the immune response elicited by plasmid. 27 In addition, substantial immune responses achieved through intra-lymph node immunization with peptide and a TLR agonist were a prerequisite for effective control of tumor progression in immune-competent mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the preclinical immunogenicity of this approach was superior to immunization using conventional means, 22 the immunological and clinical effects in humans were quite limited. 20,21 More recently, we showed in a preclinical model that an epitope-specific peptide boost after DNA vaccination achieved a significant amplification of the immune response elicited by plasmid. 27 In addition, substantial immune responses achieved through intra-lymph node immunization with peptide and a TLR agonist were a prerequisite for effective control of tumor progression in immune-competent mice.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Previously, in an attempt to improve on the in vivo generation and amplification of TAA-specific T cells, we clinically evaluated the intra-lymph node administration of two individual plasmids encompassing either MART-1/Melan-A or tyrosinase antigen fragments in stage-III and IV melanoma patients with measurable disease. [20][21][22] Nevertheless, despite an apparent correlation between immunity and clinical outcome (as measured by time to progression), 20 there were no objective clinical responses (defined by RECIST criteria) in any of these phase-I trials. Evidence from preclinical 23 and clinical studies, especially those involving adoptive T-cell therapy, 9,10 suggested that a robust, continuous presence of TAAspecific T cells with minimal interference by immune inhibitory mechanisms was a prerequisite for an objective tumor response.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…We note that the clinical feasibility of LN injections in humans is well established from a number of clinical trials (2,8,9), and safe, injectable biomaterials are available that can encapsulate both small molecule and macromolecular cargos. These factors make the approach described here attractive as a general strategy for engineering the LN microenvironment not only for vaccination but also for therapeutic contexts, such as cancer immunotherapy or immunomodulation for allergy or autoimmune disorders.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have demonstrated as much as 10 6 -fold reductions in antigen dose (5,6), 100-fold reductions in adjuvant dose (7), and enhanced protection with reduced side effects relative to traditional parenteral immunizations (2). Lymph node injection in humans is readily performed using ultrasound guidance, and the promise of i.LN vaccination has been demonstrated in recent clinical trials (2,8,9).…”
mentioning
confidence: 99%